-5x+13y=-11

Simple and best practice solution for -5x+13y=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+13y=-11 equation:


Simplifying
-5x + 13y = -11

Solving
-5x + 13y = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13y' to each side of the equation.
-5x + 13y + -13y = -11 + -13y

Combine like terms: 13y + -13y = 0
-5x + 0 = -11 + -13y
-5x = -11 + -13y

Divide each side by '-5'.
x = 2.2 + 2.6y

Simplifying
x = 2.2 + 2.6y

See similar equations:

| 7/20+x=17/20 | | 2v^2+8v-87=3 | | m/6=n | | -3k+5k=32 | | 5/9+x=11/9 | | m+10=n | | N/2+7=-10 | | 4w+6=9(w-1) | | C-6=0 | | x-3/16=7/8 | | e^2-3x=1280 | | h+3h+4hh=100 | | 2a^2-20a-88=-10 | | 2(x+5)-8=-2 | | 30-1/2n=11 | | x^2-2*xy-8*y^2+1=0 | | 1/5+x=7/20 | | -53x-5x=94-12x | | 6x-16=4x+6 | | x^2-2*xy-8*y^2=0 | | 0.55n=11 | | 11z-19z=24 | | x^2-2*xy-8*y^2+1=1 | | 6(x+2)-76=-142 | | log(16-x)=2 | | x-7/6=13/3 | | 35=3w-10 | | 25a^3+110a^2-75a= | | -7/6y=49 | | f(x)=x^2+12x+36 | | 16.3k+19.2=-64.1 | | 8z-15-(-3z)=-15 |

Equations solver categories